‘Japan Fight. Aboriginal People Fight. European People Fight’: Yolngu Stories from World War II - Riseman, Noah (The Australian Journal of Indigenous Education, 2008)
Abstract Did you know that a Bathurst Islander captured the first Japanese prisoner of war on Australian soil? Or that a crucifix saved the life of a crashed American pilot in the Gulf of Carpentaria? These are excerpts from the rich array of oral histories of Aboriginal participation in World War II. This paper presents “highlights” from Yolngu oral histories of World War II in Arnhem Land, Northern Territory. Using these stories, the paper begins to explore some of the following questions: Why did Yolngu participate in the war effort? How did Yolngu see their role in relation to white Australia? In what ways did Yolngu contribute to the security of Australia? How integral was Yolngu assistance to defence of Australia? Although the answers to these questions are not finite, this paper aims to survey some of the Yolngu history of World War II.